2016
DOI: 10.1681/asn.2015060676
|View full text |Cite
|
Sign up to set email alerts
|

Caspase-1, but Not Caspase-3, Promotes Diabetic Nephropathy

Abstract: Glomerular apoptosis may contribute to diabetic nephropathy (dNP), but the pathophysiologic relevance of this process remains obscure. Here, we administered two partially disjunct polycaspase inhibitors in 8-week-old diabetic (db/db) mice: M-920 (inhibiting caspase-1, -3, -4, -5, -6, -7, and -8) and CIX (inhibiting caspase-3, -6, -7, -8, and -10). Notably, despite reduction in glomerular cell death and caspase-3 activity by both inhibitors, only M-920 ameliorated dNP. Nephroprotection by M-920 was associated w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
100
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 103 publications
(109 citation statements)
references
References 34 publications
8
100
1
Order By: Relevance
“…These findings suggest that CASP1 may be a better explanatory marker for an adverse prognosis of DN. Activation of NLRP3 and caspase 1 may have led to maturation of inflammatory cytokines and induction of pyroptosis in an animal model . Pyroptosis in DK has been suggested to indicate an adverse prognosis of DN, at least in animal models, and the present observation replicates the phenomenon in humans.…”
Section: Commentssupporting
confidence: 75%
“…These findings suggest that CASP1 may be a better explanatory marker for an adverse prognosis of DN. Activation of NLRP3 and caspase 1 may have led to maturation of inflammatory cytokines and induction of pyroptosis in an animal model . Pyroptosis in DK has been suggested to indicate an adverse prognosis of DN, at least in animal models, and the present observation replicates the phenomenon in humans.…”
Section: Commentssupporting
confidence: 75%
“…5a). We therefore turned our attention to inflammatory cell death mechanisms as it has been shown that defect in non-inflammatory cell death can shift towards inflammatory cell death pathways including pyroptosis 25,26 . We found that cleaved caspase1, the key player in pyroptosis, was increased in APOL1 transfected cells.…”
Section: Resultsmentioning
confidence: 99%
“…Those that do, obtain inconclusive results. [60][61][62][63][64] Convincing evidence was demonstrated for renal fibroblasts. 65 Others conclude on inflammasome activation from immunostaining or transcript analysis, [66][67][68] which is inadequate given the post-transcriptional nature of inflammasome activity.…”
Section: Data In Renal Cells: Expression Releasementioning
confidence: 99%
“…21 The published data become conflicting when reporting pro-IL-1b processing and IL-1b release from renal parenchymal cells. 60,61 Only a few studies demonstrate the secretion of mature IL-1b from immune cell-free tissue specimens or from nonimmune renal cell cultures by ELISA and western blot. Those that do, obtain inconclusive results.…”
Section: Data In Renal Cells: Expression Releasementioning
confidence: 99%
See 1 more Smart Citation